Framing Contraceptive Use Motivations Among Adolescents and Young Adults Living in Informal Settlements in Kira Municipality, Wakiso District, Uganda - Mulubwa, Chama; Munakampe, Margarate Nzala; Namakula, Hilda; Hernandez, Alison; Ssekamatte, Tonny; Atuyambe, Lynn M.; Birabwa, Catherine; Chemonges, Denis; Namatovu, Fredinah; Makumbi, Fredrick; Tetui, Moses (Frontiers in Global Women's Health, 2021)
Introduction: The use of contraceptives among adolescents and young adults is one of the most cost-effective strategies to address many sexual and reproductive health (SRH) challenges, including unintended pregnancies, early marriages, and sexually transmitted infections. Despite a high burden of SRH challenges, uptake and unmet needs of modern contraceptives remain low in Uganda, especially among adolescents and young adults in informal settlement settings. This study aimed to explore the motivations of adolescents and young people to use modern contraceptives (or not). Methods: We analysed qualitative data from eight focus group discussions with 88 adolescents and young people aged 18–24 years residing in informal settlements of urban communities in Kira Municipality of Wakiso district, Uganda. Results: Motivations for use (or not) of modern contraceptives were framed by two interrelated constructs, sources of information on contraception and the unacceptable use of contraceptives among adolescents widespread in the community. These two, in turn, formed the scope of knowledge upon which adolescents and young people based their decision on whether or not to access and use modern contraceptives. Conclusion: To be more effective, sexual and reproductive health programs and interventions that aim to motivate the use of modern contraceptives among adolescents and young people in informal settings should be more comprehensive and focused on alleviating individual, health systems, social, religious factors that reinforce negative health-seeking behaviours towards contraceptive use. In addition, there is a need to support adolescents and young people with socio-economic empowering strategies that equip them with sufficient resources to choose contraceptives of their choice.